2016
DOI: 10.5114/jcb.2016.60590
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric study for cervix carcinoma treatment using intensity modulated radiation therapy (IMRT) compensation based on 3D intracavitary brachytherapy technique

Abstract: PurposeIntensity modulated radiation therapy (IMRT) compensation based on 3D high-dose-rate (HDR) intracavitary brachytherapy (ICBT) boost technique (ICBT + IMRT) has been used in our hospital for advanced cervix carcinoma patients. The purpose of this study was to compare the dosimetric results of the four different boost techniques (the conventional 2D HDR intracavitary brachytherapy [CICBT], 3D optimized HDR intracavitary brachytherapy [OICBT], and IMRT-alone with the applicator in situ).Material and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…17 Yin et al reported that an intensitymodulated radiation therapy (IMRT) PMB, in addition to ICRT, offered low organ-at-risk doses, and recommended its use in cases where ISBT was not feasible. 18 Cheng et al reported on the use of a simultaneous integrated boost to the parametrium using IMRT or VMAT. Either technique offered better dosimetry than the traditional midline block.…”
Section: Discussionmentioning
confidence: 99%
“…17 Yin et al reported that an intensitymodulated radiation therapy (IMRT) PMB, in addition to ICRT, offered low organ-at-risk doses, and recommended its use in cases where ISBT was not feasible. 18 Cheng et al reported on the use of a simultaneous integrated boost to the parametrium using IMRT or VMAT. Either technique offered better dosimetry than the traditional midline block.…”
Section: Discussionmentioning
confidence: 99%
“…When interdigitated, chemotherapy should be administered on an EBRT day and not on a brachytherapy day to avoid potential for increased complications [ 5 ]. Superior dosimetric coverage of parametrium has been reported after addition of intensity modulated radiotherapy (IMRT) [ 10 ] or interstitial brachytherapy (ISBT) [ 11 ] with intracavitary brachytherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, if such displacement occurs intra-fractionally, one should expect dose variation of similar magnitude as well as shown by some recent studies [ 15 , 16 ]. Some studies have looked into the geometric displacement, anatomic change, and other effect in each fraction of image-guided brachytherapy [ 17 , 18 , 19 , 20 , 21 ]. Monitoring of applicator motion relative to patient is therefore important in MR/CT-guided HDR brachytherapy.…”
Section: Purposementioning
confidence: 99%